Antimicrobial Peptides: Delivery by Dendritic Mesoporous Silica Nanoparticles Enhances the Antimicrobial Activity of a Napsin‐Derived Peptide Against Intracellular Mycobacterium tuberculosis (Adv. Healthcare Mater. 14/2021). Issue 14 (21st July 2021) - Beitzinger, Bastian; Gerbl, Fabian; Vomhof, Thomas; Schmid, Roman; Noschka, Reiner; Rodriguez, Armando; Wiese, Sebastian; Weidinger, Gilbert; Ständker, Ludger; Walther, Paul; Michaelis, Jens; Lindén, Mika; et al.
Abstract : In article number 2100453 by Steffen Stenger, Mika Lindén, and co‐workers, the activity of the antimicrobial peptide NapFab against intracellular Mycobacterium tuberculosis (Mtb) is significantly increased by loading onto dendritic mesoporous silica nanoparticles (DMSN). This enhanced activity is based on a 30‐fold increased, DMSN‐mediated peptide uptake. Livecell fluorescence microscopy and electron microscopy reveal fast DMSN uptake in endosomal vesicles, intracellular degradation of the carrier, and a continuous peptide release.